Analysis of Landslide Potential Using Resistivity, Geology and Climatology Values in Samangki Village, Simbang District, Maros Regency - Ahmad Haan; Ayusari Wahyuni; Muh. Said. L; Rahmaniah Fisika (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
Research has been carried out that aims to determine the analysis of landslide potential using resistivity, geology, and climatology values in Samangki Village, Simbang District, Maros Regency.This study uses the resistivity method of the wenner configuration on three tracks of 120 meters at a distance between the electrodes of 10 meters. Interpretation results obtained resistivity values on the first track between 61,1-972 W.m, on the second trajectory of 58,2 - 666 W.m, and on the last track the resistivity value of the range 60,1 - 1105 W.m, which indicates the presence of limestone inserts sandstone and aquiver scattered on each track. Then combined with secondary data in the form of rainfall maps, geological maps and soil type maps. The results of the analysis then show that the location of this research is in an area prone to landslides according to primary data or field data and secondary data from the five parameters mentioned above.